2012
DOI: 10.1259/dmfr/21358271
|View full text |Cite
|
Sign up to set email alerts
|

Marker-free registration for the accurate integration of CT images and the subject's anatomy during navigation surgery of the maxillary sinus

Abstract: Objective: This study compared three marker-free registration methods that are applicable to a navigation system that can be used for maxillary sinus surgery, and evaluated the associated errors, with the aim of determining which registration method is the most applicable for operations that require accurate navigation. Methods: The CT digital imaging and communications in medicine (DICOM) data of ten maxillary models in DICOM files were converted into stereolithography file format. All of the ten maxillofacia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…O processo de registro, uma etapa primordial a qual possibilita a sincronização das coordenadas das estruturas anatômicas do paciente com as do exame de imagem na plataforma de navegação, é o maior contribuinte para erros nas cirurgias guiadas por imagem quando manipulado de maneira equivocada (KANG et al, 2012). Recentemente, uma nova modalidade alternativa de registro composta pelo software de reconhecimento facial se mostrou como um método promissor.…”
Section: Discussionunclassified
“…O processo de registro, uma etapa primordial a qual possibilita a sincronização das coordenadas das estruturas anatômicas do paciente com as do exame de imagem na plataforma de navegação, é o maior contribuinte para erros nas cirurgias guiadas por imagem quando manipulado de maneira equivocada (KANG et al, 2012). Recentemente, uma nova modalidade alternativa de registro composta pelo software de reconhecimento facial se mostrou como um método promissor.…”
Section: Discussionunclassified
“…Computation time must be taken into account during registration especially in navigation surgery and some treatments required high real-time. 26 High resolution images have a great impact on computation time. In the experiments, using high resolution images will increase the computation time by two to three times.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu and colleagues [ 29 ] used an occlusal splint for registration in mandibular angle oblique-split osteotomy with good results; however, the system could not be used in edentulous patients and the markers were limited to the lower half of the face. A study using markerless registration showed variations between three different methods based on anatomic landmarks such as the zygoma, sinus posterior wall, molar alveolar, premolar alveolar, lateral nasal aperture and the infra-orbital areas that were used during navigational surgery of the maxillary sinus [ 30 ]. The results of that study showed that although the use of skin adhesive markers and anatomic landmarks was noninvasive and practical, it had limited accuracy and was restricted to craniofacial surgery.…”
Section: Discussionmentioning
confidence: 99%